2005
DOI: 10.1002/ejic.200500135
|View full text |Cite
|
Sign up to set email alerts
|

The N‐Lithiation of 2,4,6‐Triphenylborazine

Abstract: Keywords: Lithium / Boron / Deprotonation reactions / TetraphenylborazinatesThe reaction of the borazine Ph 3 B 3 N 3 H 3 , 1, with a diethyl ether solution of LiMe/LiI/TMEDA yields [(Ph 4 B 3 N 3 H 3 )Li-(tmeda)LiI(tmeda)], 2. However, when halide free LiMe is used in the presence of TMTA, then (Ph 4 B 3 N 3 H 3 )Li(tmta), 3, is formed which shows that a Me/Ph exchange occurs with the formation of LiPh which adds to 1 to form the borazinate 3. A Bu/Ph exchange is also observed in the reaction of 1 with LitBu/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…This indicates that a Li/Br exchange occurs during the reaction, and this also occurs during the reaction of Li 2 Pmes with 4, as shown by the formation of compounds A-F, which is also accompanied by the formation of small amounts of bicylo[1.1.0]tetraphosphanes. The tetra(borazinyl)cyclotetraphosphane (19) shows only one 31 P signal (δ = 63 ppm),which fits nicely with the other 31 P data recorded for cyclotetraphosphanes of the type (R 2 NP) 4 . [26] As far as we are aware the exchange of organo substituents in organophosphorus chemistry is not common, although the borazinyl group, with its P-N bond, is a species with higher bond polarity and is therefore more likely to be more reactive, similar to the aminophosphanes.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This indicates that a Li/Br exchange occurs during the reaction, and this also occurs during the reaction of Li 2 Pmes with 4, as shown by the formation of compounds A-F, which is also accompanied by the formation of small amounts of bicylo[1.1.0]tetraphosphanes. The tetra(borazinyl)cyclotetraphosphane (19) shows only one 31 P signal (δ = 63 ppm),which fits nicely with the other 31 P data recorded for cyclotetraphosphanes of the type (R 2 NP) 4 . [26] As far as we are aware the exchange of organo substituents in organophosphorus chemistry is not common, although the borazinyl group, with its P-N bond, is a species with higher bond polarity and is therefore more likely to be more reactive, similar to the aminophosphanes.…”
Section: Discussionsupporting
confidence: 67%
“…There is also one molecule of hexane in the unit cell. In a first attempt we solved the structure by assuming that the crystal might have the composition P 4 (H 2 N 3 B 3 Me 3 ) 4 . The structure solution indeed revealed a cyclotetraphosphane ring, with each of the four P atoms carrying a six-membered ring.…”
Section: X-ray Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[63,65,66] More recently, it has been shown that the BN bonds of borazines can become quite unequal by binding one N atom to a Li, Al, Si, P, As or Sb atom. [21][22][23][24] Also, borazinium cations, e.g. (Me 3 B 3 N 3 H 4 ) + , show three different BN bond lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Other areas consist of N-or B-metallated borazines. [21][22][23][24][25][26] Several of these borazine derivatives possess nonplanar borazine rings and also their B-N bond lengths become different, i.e. the B 3 N 3 rings are distorted.…”
Section: Introductionmentioning
confidence: 99%